Fibrin Clot Delivery System for Meniscal Repair - Jang, Suk Hwan; Ha, Jeong Ku; Lee, Dong Won; Kim, Jin Goo (Knee Surgery and Related Research, 23(3), 2011)
As meniscal preservation particularly in younger active individuals with a symptomatic meniscal tear remains the preferred treatment option, various methods have been suggested to increase healing and success rates after meniscal repair. The recent increase in clinical use of platelet rich plasma has contributed to the increased use of fibrin clot, which virtually has the same healing property. However, despite the relative ease of acquisition and preparation of fibrin clots, delivering it to the desired target area arthroscopically is challenging. Therefore, we report with a pertinent literature review a novel method of planting a fibrin clot to the desired area of meniscal tear arthroscopically using our delivery system to enhance healing.